Effect of a compassion fatigue resiliency program on nurses' professional quality of life, perceived stress, resilience: A randomized controlled trial. (3rd October 2020) - Pehlivan, Tuğba; Güner, Perihan
Abstract: Aims: This study aimed to conduct a short‐ and long‐term Compassion Fatigue Resiliency Program and compare its impact on nurses' professional quality of life, perceived stress, and resilience. Design: The research was conducted between January 2017 January 2019 as a randomized controlled trial. Methods: The sample comprised 125 oncology–haematology nurses randomly assigned to a Experimental I, Experimental II, or control group. The Compassion Fatigue Resiliency Program was conducted with the nurses as an intervention. Experimental I received a short‐term program (5 hr per day for 2 days, 10 hr in total) while Experimental II received a long‐term one (5 weeks, 2 hr per week, 10 hr in total). Measurements were obtained during pre‐ and post‐test and at 3‐, 6‐, and 12‐month follow‐ups. Research hypotheses were analysed using multilevel models. Results: The results of multilevel model analyses showed there was no statistically significant difference between mean scores for compassion fatigue, burnout, perceived stress, and resilience of nurses in the short‐ or long‐term groups or of those in the control group. Mean compassion satisfaction scores of nurses in the short‐ or long‐term groups were significantly higher than those in the control group. Mean compassion satisfaction scores of nurses in the short‐ or long‐term groups were significantly higher than the control group's pre‐test mean after 6 and 12 months. Conclusion: This study concluded that short‐ or long‐term programs had no influence on compassion fatigue, burnout, perceived stress, and resilience; however, both programs positively affected compassion satisfaction. We recommend that further studies be conducted, which will help determine the effectiveness of new programs. Impact: Caring for patients with cancer can generate work‐related stress that can negatively affect oncology nurses' physical and emotional health, which could lead to compassion fatigue. The program provided nurses with an opportunity to improve their compassion satisfaction. Because there was no difference between both programs regarding mean compassion satisfaction scores, a short‐term program may be preferred to encourage more participation among nurses. We also recommend further studies should be conducted that include environmental improvements along with the training programs. Trial registered at ClinicalTrials.gov (The name of the trial register: Effect of a Compassion Fatigue Resiliency Program; the clinical trial registration number: NCT04372303). 摘要: 目的: 本研究旨在展开一项短期及长期同情疲劳恢复计划, 并比较两项计划对护士职业生活质量、感知压力和恢复力的影响。 设计: 本研究于2017年1月至2019年1月间进行, 为随机对照试验。 方法: 试验样本为125名肿瘤‐血液科护士, 这些护士被随机分配到实验一组、实验二组或对照组。同情疲劳恢复计划的干预对象为护士。对实验一组进行短期试验(每天5小时, 为期2天, 共计10小时), 而对实验二组进行长期试验(5周, 每周2小时, 共计10小时)。分别在试验前、试验后以及随访3个月、6个月和12个月时进行测量。此外, 应使用多级模型, 对研究假设进行分析。 结果: 多水平模型分析结果显示, 短期组、长期组和对照组护士的同情疲劳、倦怠、感知压力和恢复力的平均得分没有明显的统计学差异。短期组和长期组护士的平均同情满意度得分明显高于对照组。6个月和12个月后, 短期组和长期组护士的平均同情满意度得分明显高于对照组的测试前平均值。 结论: 研究结论为, 短期或长期项目对同情疲劳、倦怠、感知压力和恢复力没有任何影响;然而, 这两个项目都对同情心满意度有积极影响。我们建议展开进一步的研究, 从而帮助确定新方案的有效性。 影响: 肿瘤科护士在照顾癌症患者时, 会产生与工作相关的压力, 从而对自身的身心健康产生负面影响, 最终导致同情疲劳。这个项目的实施可以帮助护士提高同情心满意度。两个项目在平均同情满意度得分方面没有任何差异, 因此, 可能更倾向于采用短期项目, 以便鼓励护士更多地参与。此外, 我们建议在开展培训项目的同时展开进一步研究, 包括改善环境。 在网站ClinicalTrials.gov上试验注册(试验注册名称:同情疲劳恢复计划的影响;临床试验注册号:NCT04372303)。